KARAKTERISTIK PENGGUNAAN TINDAK TUTUR DIREKTIF DALAM PEMBELAJARAN DI MADRASAH ALIYAH PUTRI AISYIYAH PALU - Afriansyah, Afriansyah (BAHASANTODEA, 2016)
This research aims at describing the characteristics of directive speech act usage cover (1) form, (2) function and (3) strategy of instructional at Madrasah Aliyah Putri Aisyiyah Palu. The data source was obtained from teacher and students’ speech act when learning process occurred. Approach used was pragmatic approach. Method employed was descriptive qualitative. Data were collected through two techniques, was namely (1) recording and (2) observation. The subjects were teacher and students of Madrasah Aliyah Putri Aisyiyah Palu. Technique of data analysis was interactive model. Analysis of this research covered four stages, namely: (1) data collection, (2) data reduction, (3) data display and (4) verification/drawing conclusion. The research results reveal that learning process at Madrasah Aliyah Putri Aisyiyah Palu consists of (1) command form, (2) inviting form, (3) asking for form, (4) pleasing form, (5) prohibition form, (6) refusing form, (7) question form and (8) statement form. The function of directive speech act of the research consists of: (1) command function, (2) inviting function, (3) asking for function, (4) pleasing function, (5) prohibition function and (6) refusing function. Command function is for commanding, recommending, increasing concentration of the students, testing students’ understanding, (2) inviting function is for invitation, recommendation, increasing students’ concentration, (3) request function is for requesting, offering, conducive a situation, testing students’ understanding, (4) pleasing function is for pleasing, allowing, increasing students’ understanding, (5) prohibition function is for prohibition, prevention, conducive a situation and (6) refusing function is for refusing, limiting explanation, avoiding. Strategies used in directive speech act were direct and indirect strategy. The direct strategy comprised (1) direct command, (2) direct inviting, (3) direct requesting, (4) direct pleasing, (5) direct prohibition and (6) direct refusing. Meanwhile, indirect strategy comprised (1) indirect question and (2) indirect statement with various functions that referred behind the speech depend on the context.